Profit in Liberal Professionals. A Human Right and an Unconstitutional Tax - Sánchez, Juan Diego Sánchez (2019)
The present article first analyses the definition of money as an object of private appropriation, then, the concept of the human right to private property as a protector of the domain of goods and, finally, the tax directly levied on the generation of profit by independent professionals. For the preparation of the article, the main results and data obtained from the author's bachelor's thesis in Law are extracted and expanded. Likewise, during the research process a questionnaire was used, which was applied to the sample of active or inactive lawyers registered in the country. The sample was based on information given by the Bar Association for 2018 about the lawyers associated. A documentary review was also conducted to analyse the tax and legal doctrine, textbooks, laws, and other national and supranational norms, such as the Declaration of Human Rights, related to the work carried out and from which the most important concepts were extracted. The results of the work are reliable and well-argued, in particular, thanks to the statistical validation of the applied instrument. Among the main conclusions, details are given on money as a legal good, object of private property, private profit as a form of appropriation of money, legal protection of money, principles of reasonableness, proportionality and non‑confiscation, the fact generating income tax to individuals with lucrative activity, and, finally, private profit as a human right.